Localise this Tooth in The Sinus - Kaustubh Sansare (Wolters Kluwer Medknow Publications, 2004)
This is a serious section designed to test your diagnostic skill. Periodically we will bring to you clinical and radiographic pictures for you to test your diagnostic acumen. So remember to come back and see what's new in the Grey Area's.